Impact of complete surgical resection on outcome in aggressive non‐Hodgkin lymphoma treated with immunochemotherapy. (14th September 2020) - Schmitz, Christine; Rekowski, Jan; Müller, Stefan P.; Farsijani, Navid; Hertenstein, Bernd; Franzius, Christiane; von Verschuer, Ulla; La Rosée, Paul; Freesmeyer, Martin; Wilop, Stefan; Krohn, Thomas; Raghavachar, Aruna; et al.
Abstract: Background: Surgical resection is considered to be of purely diagnostic value in aggressive lymphoma. Evidence for an impact on outcome is scant and restricted to retrospective observations. Methods: In the "Positron Emission Tomography‐guided Therapy of Aggressive non‐Hodgkin Lymphomas" (PETAL) trial, patients with a negative baseline positron emission tomography (PET) scan were documented in a prospective observational substudy. Baseline PET‐negative patients with the absence of lymph node enlargement on computed tomography and a negative bone marrow biopsy were considered to have undergone complete lymphoma resection. Results: Eighty‐two of 1, 041 patients (7.9%) had a negative baseline PET scan, and 67 were included in this analysis. All were treated with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP), plus rituximab for CD20‐positive lymphomas. Among 52 patients with diffuse large B‐cell lymphoma (DLBCL), 48 had completely resected disease. Their outcome tended to be better than that of 115 baseline PET‐positive stage I DLBCL patients treated in the main part of the PETAL trial (2‐year progression‐free survival 92.7% [95% confidence interval 84.7‐100] versus 88.4% [82.5‐94.3], P  = .056; 2‐year overall survival 92.7% [84.7‐100] versus 93.7% [89.2‐98.2], P  = .176), but this was restricted to patients below the age of 60 years (2‐year progression‐free survival 100% versus 92.2% [84.8‐99.6], P  = .031; 2‐year overall survival 100% versus 95.9% [90.2‐100], P  = .075). In peripheral T‐cell lymphoma, eight of 11 patients had completely resected disease. In contrast to DLBCL, complete resection was not associated with improved outcome compared to the control. Conclusion: Young patients with early stage DLBCL may benefit from complete lymphoma resection prior to immunochemotherapy. Abstract : In stage I diffuse large B‐cell lymphoma outcome was better after complete than incomplete lymphoma resection. In contrast to B‐cell lymphoma, no benefit for complete resection was seen in T‐cell lymphoma.